Regional voting dynamics in Europe: The rise of anti-elite and anti-European parties. (September 2020) - Ferrante, Chiara; Pontarollo, Nicola
In this paper, votes registered by parties with a high anti-elite and anti-European salience are mapped, in order to identify potential geographical patterns in European regions.